Large Language Model Framework for Device Orchestration in Low-Code No-Code Solutions - Punithavel, Rohith Kumar; Deeksha Sivakumer (International Journal of Computational and Experimental Science and Engineering, 2025)
In today's digital era, virtually every aspect of life or industry is influenced by digital services. Digital devices have played a critical role in transforming various fields, from education to healthcare, by enhancing availability and access. They have also helped prevent theft, robbery, and even property damage. They have also contributed to crime prevention, including theft, robbery, and property damage. With exponential growth, digital device manufacturers serving similar or different purposes have created a heterogeneous digital ecosystem to offer ease-of-use solutions. However, this heterogeneity poses challenges even for software developers. Beyond software developers, a growing number of professionals from other engineering streams, management, and small to medium-sized business owners are required to interact with digital systems. Low-code and no-code platforms have emerged as viable solutions to support this shift and encourage these users to manage digital services without complex programming. The Low-Code and No-Code platforms have limitations but are not limited to flexibility, usability, and integration, which restrict the development of customized solutions. Large Language Models have recently drawn everyone's attention due to their cognitive ability and capability to bridge gaps. In this paper, we explore how LLMs can enhance Low-Code and No-Code platforms by facilitating the integration of digital devices and improving the management of their usage and services.